PERANAN PEREMPUAN PESISIR DALAM MENINGKATKAN EKONOMI RUMAH TANGGA - Fitri Rahmawati; Elly Karmeli (Fakultas Ekonomi dan Manajemen, 2022)
This study aims to determine the role of coastal women in Labuhan Sumbawa Village, Labuhan Badas District in optimizing their position as not only housewives but also being able to help improve the household economy. This research is descriptive. Research informants consisted of the head of the PKK, village officials, community leaders and the people of Labuhan Sumbawa Village. Data was collected by using observation, interview, and documentation techniques. Data analysis was carried out using Miles and Huberman qualitative data analysis techniques, including data reduction, data presentation, conclusion drawing/verification. The results showed that the role of women in Labuhan Sumbawa Village was not only being a housewife but also participating in increasing their family's household income. The participation of coastal women in Labuhan Sumbawa Village is by having a side business in order to improve family welfare. The participation of coastal women in Labuhan Sumbawa Village is manifested in the housewife sector, trading, as well as social activities. The need for coastal women to improve their business is the need for business capital assistance for home industries so that the quality of the product can support family income. There needs to be a special auction place provided by the government so that the price of fish increases so that household income increases. If household income increases, coastal women no longer need to do activities outside the home.